Teacher Strategies in Building Learning Motivation in Street Children - Maulana, Dita Taufik; Ismail, Teuku (Jurnal Pendidikan Amartha, 2022)
The purpose of this study was to determine the teacher's strategy in building the learning motivation of street children in the ERBE Foundation tutoring and the inhibiting factors in building the learning motivation of street children at the ERBE Foundation. The type of research used in this study is a qualitative research with a descriptive approach. Data collection techniques in the form of observation, interviews, documentation and audio-visual materials. Data calibration techniques used in this study are audit trial, member check, triangulation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research findings indicate that the strategies used by teachers in building children's motivation use various methods. In building motivation, The teacher uses an approach by knowing the child's interests, numbers, giving praise and gifts. Factors that become obstacles in building children's motivation such as children who are lazy, parents who don't care about their children's education, the influence of the environment in which they live and the number of educators at the ERBE Foundation.